2011
DOI: 10.1093/infdis/jir786
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Model of Necrotic Tuberculosis Granulomas Develops Hypoxic Lesions

Abstract: We demonstrate that tuberculosis lesions in C3HeB/FeJ are hypoxic. Activities of some key tuberculosis drug regimens in development are represented differently in C3HeB/FeJ versus BALB/c mice. Because C3HeB/FeJ display key features of human tuberculosis, this strain warrants evaluation as a more pathologically relevant model for preclinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
209
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(225 citation statements)
references
References 28 publications
8
209
0
Order By: Relevance
“…The pneumonic distribution is common among M.tb-infected mice. 1,8,21,34 Necrosis, neutrophils, and bronchiolar exudate characterized the second pattern. Necrotic foci contained basophilic nuclear debris (not shown) or lightly eosinophilic macrophage ''ghosts'' consistent with caseation necrosis 25,29 (Fig.…”
Section: Features Of Pulmonary Tb Disease In Cba/j Micementioning
confidence: 96%
See 1 more Smart Citation
“…The pneumonic distribution is common among M.tb-infected mice. 1,8,21,34 Necrosis, neutrophils, and bronchiolar exudate characterized the second pattern. Necrotic foci contained basophilic nuclear debris (not shown) or lightly eosinophilic macrophage ''ghosts'' consistent with caseation necrosis 25,29 (Fig.…”
Section: Features Of Pulmonary Tb Disease In Cba/j Micementioning
confidence: 96%
“…Fibrotic, cell-poor granulomas associated with healed primary M.tb infection in humans 25 were absent in CBA/J mice, and that absence is consistent across mouse strains. 1,8,21,34 Collagen, Mineral, and M.tb Bacilli in CBA/J Lungs With TB Disease…”
Section: Features Of Pulmonary Tb Disease In Cba/j Micementioning
confidence: 99%
“…C57Bl/6 mice do not faithfully reproduce certain aspects of human TB. In contrast, Mtb-infected C3HeB/FeJ mice display lesions with prominent necrotic degeneration, thus more closely resembling human granulomas (11)(12)(13)(14)(15). Harper and colleagues first demonstrated that tubercle lesions in this model develop hypoxia (15).…”
Section: Clinical Relevancementioning
confidence: 99%
“…In the setting of pulmonary tuberculosis (TB), the sessile organisms are insulated in sac-like granuloma lesions, somewhat similar to encasement in biofilm observed in in vitro cultures [6][7][8]. During TB chemotherapy with rifampicin and isoniazid, planktonic bacteria are killed rapidly (within 2 weeks), whilst eradication of sessile organisms necessitates extended exposure to higher concentrations of these agents [1,4,9].…”
mentioning
confidence: 93%